2020
DOI: 10.1117/1.nph.7.2.025005
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal-scanning attenuated total reflection terahertz imaging for biological tissues

Abstract: Significance: Terahertz wave is a potential tool for biological tissues due to its noninvasiveness and high sensitivity to water. Attenuated total reflection (ATR) with the characteristics of high sensitivity and nondestruction has been applied for THz imaging. Aim: We aim to develop an imaging methodology to facilitate practical application of THz ATR imaging. Approach: We have demonstrated a horizontally scanning THz continuous wave ATR imaging system. The effective imaging area was as large as the prism ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…Second, to enhance the accuracy of the tumor margins delineation, in ref. 87 , a region-of-interest (ROI) segmentation method was developed for work with the 2.52 THz CW imaging system. This method combines a variety of signal processing techniques, including the block matching 3D denoising, fuzzy c-means clustering, morphology operation, and canny edge detection.…”
Section: −20 35mentioning
confidence: 99%
“…Second, to enhance the accuracy of the tumor margins delineation, in ref. 87 , a region-of-interest (ROI) segmentation method was developed for work with the 2.52 THz CW imaging system. This method combines a variety of signal processing techniques, including the block matching 3D denoising, fuzzy c-means clustering, morphology operation, and canny edge detection.…”
Section: −20 35mentioning
confidence: 99%
“…There have also been some other techniques based on different approaches, for example, in 2015, Doradla et al 12 demonstrated the first flexible THz waveguide-enabled endoscopic system for colorectal cancer detection; In 2020, Wu et al employed a scanning THz continuous wave ATR system to image rat brain tissues. 13 However, these new approaches still cannot detect small areas of biological tissue due to the limitation of THz beam spot sizes.…”
Section: Introductionmentioning
confidence: 99%
“…And the sample is usually covered by a flat window to reduce the diffusive reflection caused by the uneven sample surface, 11 in which, the extrusion often changes the sample morphology, resulting in deviations of signal distribution from that of the actual surface. There have also been some other techniques based on different approaches, for example, in 2015, Doradla et al 12 demonstrated the first flexible THz waveguide‐enabled endoscopic system for colorectal cancer detection; In 2020, Wu et al employed a scanning THz continuous wave ATR system to image rat brain tissues 13 . However, these new approaches still cannot detect small areas of biological tissue due to the limitation of THz beam spot sizes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the continuous development of terahertz technology, it has been gradually studied and applied in various fields: remote sensing radar [ 3 ], material structure detection [ 4 ], data transmission [ 5 ], communication [ 6 ], security [ 7 ], and counter-terrorism [ 8 ]. In biomedicine, THz waves have the characteristics of low energy and non-ionizing radiation, and it will not cause harmful damage to biological tissues or organisms [ 9 , 10 ]; therefore, THz are used to identify and distinguish various biological small molecules [ 11 ], macromolecules [ 12 , 13 , 14 ], biological information extraction [ 15 ], and drug component detection [ 16 ].…”
Section: Introductionmentioning
confidence: 99%